2022
DOI: 10.1177/16878140221075461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-hole and multi-hole orifice energy consumption

Abstract: Nowadays, with rising energy prices, energy efficiency is playing an important role in all industries. Differential pressure-based measuring instruments are still widely used instruments with orifice flow meters being the most popular ones. Due to its simplicity, reliability, and ease of maintenance, orifice flow meters are very common measuring instruments in many industries. As these instruments are differential pressure-based instruments, they are increasing energy costs due to increased pressure loss. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This finding is further corroborated by a more recent research [3], which has reported that multi-hole orifice has then tendency to accelerate pressure recovery, reduce pressure drop and increase discharge coefficient. Furthermore, compared to orifices with lower β parameters, those with higher β parameters (ratio of orifice diameter to pipe diameter) exhibited reduced power consumption and relative power loss [4].…”
Section: Introductionmentioning
confidence: 97%
“…This finding is further corroborated by a more recent research [3], which has reported that multi-hole orifice has then tendency to accelerate pressure recovery, reduce pressure drop and increase discharge coefficient. Furthermore, compared to orifices with lower β parameters, those with higher β parameters (ratio of orifice diameter to pipe diameter) exhibited reduced power consumption and relative power loss [4].…”
Section: Introductionmentioning
confidence: 97%
“…2 The presented results (pressure, velocity, and temperature profiles) match well with other results from literature and are easily applicable. On the other hand, Bikić et al 3 numerically and experimentally investigates the benefits (mostly visible in lower energy consumption) of a novel design of flow meters, typically employed in industry due to their simplicity, reliability, and ease of maintenance. Another industrial application, a transient analysis of hydropower plants, is presented in Svrkota et al 4 From a data analysis performed on 270 hydropower plants with crossflow turbines, a simple mathematical model that estimates the turbine performance characteristics is formed.…”
mentioning
confidence: 99%